Disclosure of the Mechanisms of Metabolic Disorders in Highly Productive Cows as a Way to Improve Milk Production Technology - Skachkov Dmitry (EDP Sciences, 2021)
The aim of this study was to study the molecular mechanisms of metabolic disorders that develop in highly productive cows. It was found that in the blood serum of animals with subclinical ketosis (SCK), which are in the eighth month of pregnancy, the concentration of β-hydroxybutyrate is increased, the content of iron, calcium and phosphorus is reduced, its iron-binding capacity against the background of the absence of phenomena of hepatocellular insufficiency, violation of the integrity of hepatocytes, hypoplastic anemia. The aggravation of ketoacidosis in fresh cows with rumen acidosis is facilitated by the development of carbohydrate deficiency in them, due to their increased oxidation in the reactions of anaerobic glycolysis, accompanied by excessive catabolism of purine mononucleotides to uric acid. Excessive lipid peroxidation of membrane structures under conditions of increased catabolism of purine nucleotides, along with the accumulation of acylglycerols in the liver caused by cobalamin deficiency, leads to the development of syndromes of impaired hepatocyte integrity and hepatocellular insufficiency. A decrease in the liver's ability to store iron ions and synthesize proteins that provide an increase in the iron-binding capacity of blood plasma in conditions of cobalamin deficiency contributes to the development of hypoplastic anemia not only in cows, but also in calves born from them.